Educating for the implementation of evidence-based healthcare in Brazil: the JBI methodology - Vilanice Alves de Araújo Püschel; Larissa Bertacchini de Oliveira; Eduardo Tavares Gomes; Kelli Borges dos Santos; Fábio da Costa Carbogim (SciELO, 2021)
ABSTRACT Objective: To present the JBI evidence implementation methodology and report the Brazilian experience in educating health professionals. Method: This is an experience report on professional education in the Brazilian context as per the JBI methodology. Results: In four years, 29 clinical fellows were trained in Brazil, with technical and scientific theoretical bases and tools for evidence-based practice, focusing on the transformation of the health contexts in which they are inserted. Conclusion: The JBI methodology offers systems and tools to evaluate existent practices; it also reinforces and disseminates evidence-based healthcare, potentializing the achievement of effective change in healthcare.